Digital Transformation and Efficiency of Sharia-Based HR Management on MSME Performance with Organizational Culture Moderation: A Quantitative Study in Cileungsi - Kumala, Destiana (PT Inovasi Pratama Internasional, 2024)
Digital transformation has become a crucial factor in enhancing the competitiveness of micro, small, and medium enterprises (MSMEs) in the era of globalization. Digital technology enables MSMEs to innovate, improve efficiency, and expand markets. However, many MSMEs face challenges in adopting this technology, such as limited resources and resistance to change. Sharia-based human resource management (HRM), which emphasizes justice and welfare, can provide solutions in creating a productive and harmonious work environment. This study aims to fill the gap in the literature regarding the interaction between digital transformation and Sharia HRM on MSME performance, with the moderation of organizational culture. The research method uses a quantitative approach with a case study on MSMEs in Cileungsi, involving 100 randomly selected respondents. Data were collected through questionnaires and analyzed using SEM-PLS. The SEM test results show that digital transformation and Sharia HRM have a significant effect on MSME performance. Organizational culture has a strong moderating role, strengthening the positive impact of digital transformation and Sharia HRM on MSME performance. The results indicate that the integration between digital transformation and Sharia HRM, supported by a strong organizational culture, can enhance productivity, operational efficiency, as well as employee satisfaction and motivation. This study emphasizes the importance of adopting digital technology and applying Sharia principles in HRM to improve MSME performance, with organizational culture as an essential supporting factor. These findings provide practical guidance for MSME actors in developing strategies that improve efficiency and employee welfare.